The role of collaborative workspaces in promoting networking opportunities: a comparison between urban and peripheral contexts - Lorenzo Marmo; Antonis Rovolis; Vasilis Avdikos (Regional Studies, Regional Science)
This paper aims at assessing the role of collaborative workspaces (CWS) as interaction platforms able to offer networking opportunities on different levels and with a diverse array of stakeholders. Several qualitative studies have emphasised that CWS function as focal points, providing open physical space, materials and social settings which help different actors find specific services, resources and foster their interaction. This study is the first that aims to shed light, through quantitative evidence, upon the main determinants influencing the role of CWS in urban and non-urban areas as platforms for networking opportunities on the following three dimensions: focal point on the local level; wider networks of CWS on the regional, national and international level; relationships with external actors such as medium-large firms, locally-rooted industries and with the third sector. Simple, ordered and multinomial probit models were applied in the econometric analysis using data from a survey directed to managers of CWS in Europe. Results suggest that CWS outside cities are more likely to be part of regional and national networks of similar spaces. Whereas, CWS in cities have a stronger relationship with medium-large firms, non-governmental organisation (NGOs) and they are more likely to participate in networks of CWS on the international level.